Defining Sub-Saharan Africa’s Health Workforce Needs: Going Forwards Quickly Into the Past: Comment on "Non-physician Clinicians in Sub-Saharan Africa and the Evolving Role of Physicians" - Olapade-Olaopa, E. Oluwabunmi (Int J Health Policy Manag, 2016)
Recent proposals for re-defining the roles Africa’s health workforce are a continuation of the discussions that have been held since colonial times. The proposals have centred on basing the continent’s healthcare delivery on non-physician clinicians (NPCs) who can be quickly trained and widely distributed to treat majority of the common diseases. Whilst seemingly logical, the success of these proposals will depend on the development of clearly defined professional duties for each cadre of healthcare workers (HCW) taking the peculiarities of each country into consideration. As such the continent-wide efforts aimed at health-professional curriculum reforms, more effective utilisation of task-shifting as well as the intra – and inter-disciplinary collaborations must be encouraged. Since physicians play a major role in the training mentoring and supervision of physician and non-physician health-workers alike, the maintenance of the standards of university medical education is central to the success of all health system models. It must also be recognized that, efforts at improving Africa’s health systems can only succeed if the necessary socio-economic, educational, and technological infrastructure are in place.